2016
DOI: 10.1177/0971890716670721
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Spirituality and Employee Job Behaviour

Abstract: Effective employee job behaviour is often driven by suitable work environment that continually provides a meaningful job assignment throughout one’s professional career. Recent researches in organizational studies have strengthened the notion of workplace spirituality for creating meaningful job, delight, contentment and hope at work that generate employee engagement, and organizational commitment. Such type of job behaviour is expected to produce better job performance of employees while deriving higher produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The role provides executives with components that make their work intrinsically meaningful (green blocks). Ashmos and Duchon (2000) , Pradhan and Jena (2016) . However, senior executives’ work sometimes becomes so dominantly meaningful that it can dictate their lives ( Quick et al, 2014 ), to the extent that it generates unavoidable anti-meaning (red blocks) (in the form of time constraints, high levels of work-related stress and pressure, loneliness, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The role provides executives with components that make their work intrinsically meaningful (green blocks). Ashmos and Duchon (2000) , Pradhan and Jena (2016) . However, senior executives’ work sometimes becomes so dominantly meaningful that it can dictate their lives ( Quick et al, 2014 ), to the extent that it generates unavoidable anti-meaning (red blocks) (in the form of time constraints, high levels of work-related stress and pressure, loneliness, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Organizations need to recognize that an engaged employee with meaningful assignment will naturally have a greater commitment during one’s career (Pradhan & Jena, 2016). A positive workplace encourages workers to be dedicated and innovative in order to achieve greater JS (Pradhan & Jena, 2016). Our study’s correlational results on the predicted employee job attitude (EE and organizational commitment) with WPS are in line with result of Gull and Doh (2004).…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that WPS (MW, SoC and AoV) has positive influence on the dimensions of employee job attitude (EE, OCB and JS). Organizations need to recognize that an engaged employee with meaningful assignment will naturally have a greater commitment during one's career (Pradhan & Jena, 2016). A positive workplace encourages workers to be dedicated and innovative in order to achieve greater JS (Pradhan & Jena, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this article, workplace spirituality reflects employee experiences based on meaningful work, employee relationships, solidarity and excellence in the workplace (Salarzehi et al, 2019). Workplace spirituality is defined as the psychological state in which employees believe they have a meaningful work inner life and are placed in a social context (Pradhan & Jena, 2016). Spirituality is a dogmatic, non-exclusive, gender-neutral, nonpatriarchal approach that relates to the One Source of All Being.…”
Section: Introductionmentioning
confidence: 99%